EFFORTS TO IMPROVE CREATIVITY AND ECONOMICINDEPENDENCE OF THE COMMUNITY IN LAM ISEK VILLAGE,PEUKAN BADA DISTRICT, ACEH BESAR REGENCY: UPAYA MENINGKATKAN KREATIVITAS DAN KEMANDIRIANEKONOMI MASYARAKAT DI DESA LAM ISEK KECAMATANPEUKAN BADA KABUPATEN ACEH BESAR - Nazaruddin, Nazaruddin; Fuady; Yani Prihatina Eka Furda; Tasliati Djafar; Akmal; Umar Husein Abdullah; Siti Safura; Rafiqah; Dian Rahmita Sari (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
Community Service (CS) is one of the main pillars of the tridharma of higher education, aiming to apply science and technology to provide direct benefits to society. The implementation of CS in Lam Isek Village, Peukan Bada District, Aceh Besar, focuses on skills training in sewing, making instant ginger powder, and making dragon fruit syrup. This program is designed to enhance the villagers' skills in processing local resources into value-added products to improve their economic independence. The training, involving universities such as Universitas Iskandar Muda, Universitas Serambi Mekkah, and several other institutions, successfully improved participants' abilities in sewing, producing ginger powder, and making dragon fruit syrup. As a result, participants gained new knowledge and the potential to start small home-based businesses, which can increase income and strengthen the local economy. This program has a positive impact on the welfare of the Lam Isek community and can serve as a model for future CS programs.